Postpartum Prolapsed Leiomyoma with Uterine Inversion Managed by Vaginal Hysterectomy - Kelly L. Pieh-Holder; Heidi Bell; Tana Hall; James E. DeVente (Case Reports in Obstetrics and Gynecology)
Background. Uterine inversion is a rare, but life threatening, obstetrical emergency which occurs when the uterine fundus collapses into the endometrial cavity. Various conservative and surgical therapies have been outlined in the literature for the management of uterine inversions. Case. We present a case of a chronic, recurrent uterine inversion, which was diagnosed following spontaneous vaginal delivery and recurred seven weeks later. The uterine inversion was likely due to a leiomyoma. This late-presenting, chronic, recurring uterine inversion was treated with a vaginal hysterectomy. Conclusion. Uterine inversions can occur in both acute and chronic phases. Persistent vaginal bleeding with the appearance of a prolapsing fibroid should prompt further investigation for uterine inversion and may require surgical therapy. A vaginal hysterectomy may be an appropriate management option in select populations and may be considered in women who do not desire to maintain reproductive function.